Mate tea with Lactobacillus probiotics: viability, chemical characterization and in vitro resistance to the gastrointestinal tract (Research, Society and Development, 2022)
To meet the consumer demand for functional drinks with bioactive compounds, this study aimed to evaluate the addition of Lactiplantibacillus plantarum LP299V, Lacticaseibacillus rhamnosus GG and Lactobacillus acidophilus in mate tea. The viability of the probiotic bacteria, microbiological and physicochemical characteristics, the in vitro resistance to the gastrointestinal tract and the antioxidant capacity of the mate teas were evaluated during 28 days. Unlike L. plantarum and L. rhamnosus, L. acidophilus did not remain viable in the product. The physicochemical characteristics of the teas with L. plantarum and L. rhamnosus were maintained over time. Phenolic compounds of mate tea containing L. plantarum were identified by HPLC. There was stability of phenolic compounds and flavonoid content in teas over time. At the end of the gastrointestinal assay, there was 4.52 Log CFU/mL of L. plantarum, suggesting that consumption of 100 mL of tea may provide > 6.0 Log CFU/mL of the probiotic. Mate tea can carrier L. rhamnosus and L. plantarum. There is an increase in the search by consumers for health drinks and at the same time, there is a growing demand for alternatives carriers of probiotics, due to individuals with intolerance and allergy to dairy products, vegetarians and others. This study confirms the possibility of using mate tea, widely consumed in Brazil, as a positive carrier of of L. plantarum and L. rhamnosus, making it an attractive alternative beverage to the dairy matrix.